ANTICIPATION AS A CONSCIOUS ACCELERATION OF RESPONSE TIME UNDER CONDITIONS OF INITIATIVE AND COUNTERACTION WITH THE ENEMY - Malkov, O.B.; Dementiev, V.L. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to consider the effect of anticipation on the performance of certain mental functions aimed at: reducing the response time to the enemy's influences; to reduce the time for the use of combat actions (methods) due to earlier determination of the moment of the start of an attack and automation of responses to a trigger signal. Methods and structure of the study. The study of the influence of ideomotor representations of the performance of deliberate combat actions led to the understanding of anticipation as a phenomenon characteristic of almost all mental processes of controlling motor actions. Anticipation allows, before the appearance of a favorable situation or a pre-launch and trigger signal, to already carry out mental and motor preparation for combat. Results and conclusions. As a result of the use of impromptu combat actions, anticipation makes it possible to reduce the time of the launch reaction to enemy actions, to change the temporal structure and duration of mental processes that accompany the response in combat (competitive) countermeasures. Understanding the patterns of controlling the speed of one's own reactions in combat interaction allows the athlete to respond most quickly to the trigger signal.